Management of Agricultural Receipts Circulation: Foreign Experience, Realities and Prospects for Ukraine - KHROMUSHYNA, Lyudmyla; KONIEVA, Iryna; TKACHENKO, Viktoriia; BAIDAK, Liudmyla (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020DO - 10.14505/jarle.v11.2(48).16, 2020)
The purpose of the article is to summarize the problems and present the prospects for the development of Ukraine’s agricultural sector crediting based on the management of the agricultural receipts circulation as an innovative financial tool taking into account foreign practices. The research was based on the use of the dialectical method of cognition and the systematic approach to the problem of functioning and effectiveness of crediting agriculture through the agricultural receipts in Ukraine and in the world. The following general scientific methods were applied in the research: abstract-logical, monographic, generalization. The article substantiates the feasibility of using agrarian receipts, that make it possible to invest heavily in the agricultural sector, expand the circle of participants, form the chain of relations ‘creditor – agricultural producer – buyer (trader)’. The institutional peculiarities of agrarian receipts functioning determined by their commodity or financial form, legal status of participants are specified. The review and summarization of the positive experience gained by Brazil made it possible to determine the feasibility of the development of agricultural receipts in Ukraine, where the relevant normative acts were adopted at the legislative level. Determination of the peculiarities of implementing the pilot project on the agricultural receipts introduction in Ukraine allowed outlining the main problems and prospects for further functioning and management of their circulation. The article uses up-to-date information on the results of agricultural receipts implementation in Ukraine, including ‘organic’, identifies current problems and prospects for the development of agrarian receipts tools.